Adaptation and Mitigation Strategies of Climate Change from Agricultural Sector in the Tabalong District (South Borneo) - Rian Yaitsar Chaniago; Rachmat Boedisantoso; Arie Dipareza Syafei (Jurnal Sosial Humaniora, 2022)
Agriculture and climate change have a complex causal relationship. Theagricultural sector produces large amounts of Green House Gases (GHG)such as CH4, CO2, and N2O which affect the climate. One of theconsequences of climate change is an increase in rainfall. This has caused2,971.51 ha of submerged and damaged rice fields in the Tabalong District.This study aims to determine the climate change adaptation and mitigationstrategies of the agricultural sector in the Tabalong District. Emissionmeasurements and mapping of the distribution of GHG emissions are shownto support strategy determination. The GHG inventory is calculated usingthe Indonesian Ministry of Environment and Forestry method, mapping thedistribution of emissions using the geographic information system method,and determining the best adaptation and mitigation strategies using theAnalytic Hierarchy Process (AHP) with Expert Choice Software. Theresults showed that GHG emissions from the agricultural sector of theTabalong District until 2030 amounted to 191,384 tCO2e / year. There arefive Sub-districts identified as the largest GHG-producing districts from themapping of the distribution of GHG. The results of the AHP synthesis showthat there are three strategies for climate change adaptation and fourstrategies for climate change mitigation.